2019
DOI: 10.3892/etm.2019.7821
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of short‑term intensive treatment with insulin pump to improve islet β‑cell function in newly diagnosed type 2 diabetes via inhibition of oxidative stress

Abstract: The present study (Chinese Trial Registry GTB7027) assessed the effects of short-term intensive treatment with insulin pump on islet cell function in patients with newly diagnosed type 2 diabetes and the possible mechanism. A total of 100 patients newly diagnosed with type 2 diabetes and hospitalized between January 2016 and December 2017 were divided into a control and an experimental group (n=50 in each group). The subjects of the control group were administered multiple insulin injections for intensive trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…11 Several experimental and clinical trials have shown increased ROS in DM. [12][13][14][15] Receptor activator of nuclear factor-κB ligand (RANKL) is a type II homotrimeric transmembrane protein that is expressed in various cells, including osteoblasts, periodontal ligament (PL) cells, lymphocytes, and osteocytes. 16 Its main role in bone is the stimulation of osteoclast differentiation, activity, and inhibition of osteoclast apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…11 Several experimental and clinical trials have shown increased ROS in DM. [12][13][14][15] Receptor activator of nuclear factor-κB ligand (RANKL) is a type II homotrimeric transmembrane protein that is expressed in various cells, including osteoblasts, periodontal ligament (PL) cells, lymphocytes, and osteocytes. 16 Its main role in bone is the stimulation of osteoclast differentiation, activity, and inhibition of osteoclast apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ressalta-se que poucos estudos avaliaram as isoformas da proteína SOD (SOD1 e SOD2) no DM2 (Mozzini et al, 2015;El-Gharbawy et al, 2016;Grindel et al, 2016;Sindhu et al, 2018;Sireesh et al, 2018;Liu et al, 2019) tal como foi realizado neste estudo. Ambas as isoformas de SOD estão localizadas em regiões celulares diferentes; enquanto a SOD1 está presente no citosol da célula, a SOD2 se localiza especificamente no interior da mitocôndria, uma organela amplamente afetada pelo DM2, o que ressalta a necessidade de SOD1 e SOD2 serem avaliadas de forma distinta.…”
Section: Avaliação Dos Níveis De Expressão Proteicaunclassified